The Role of Immunopathologic Mechanisms in the Pathogenesis of the Odontogenic Abscesses and the Flegmon of the Maxillofacial Area and the Collum - Batyrbekova, Fatima R. (Asian Journal of Pharmaceutics (AJP), 2018)
Pyoinflammatory diseases of maxillofacial area (MFA) are one of the most serious problems of maxillofacial surgery. The high medical and social significance of these diseases are due to their frequent occurrence in persons of working age and the risk of life-threatening complications: Bleeding from the great vessel, brain abscess, the spread of infection into the deep cellular spatium of the collum. In more than 1/3 of all patients, pyogenic lesions of MFA develop on the background of secondary immunodeficiency, accompanied by impaired regulation of the secretion of pro-inflammatory cytokines, and predisposing to prolonged smoldering flow or, on the contrary, rapid spread of inflammation with extensive tissue damage. This fact determines the importance of developing integrated approaches to diagnostics and treatment. The aim of the study is to generalize modern ideas about causative agents and their effect on the features of the inflammatory diseases of the MFA. We systematized and analyzed contemporary works of Russian and foreign authors on the study of the effects of causative agents of bacterial and viral nature and characteristic changes in the immune status. The modern data on the role of microbial factors in the development and maintenance of local and systemic immunological status disorders in case of inflammatory disease of MFA are presented, the impact on the development of bacterial and viral microflora diseases is given, with special attention paid to immunomodulatory effects of causative agents. The factors of pathogens influence most frequently associated with inflammatory diseases of theMFA and collum, as well as the relationship of individual microorganisms with the clinical manifestations of this pathology type and the detection of the pathogenetic role of immune disorders, allow to conduct studies on the formation of optimal correction schemes for each patient (personified) depending on the features of the course of the disease.